Case study of employee experience of generation Z working in the austrian electronic industry - Shan Yang (2023)
Background and purpose – Austria has encountered a talent shortage, exceedingly foreseen the demographic gap since baby boomers have started to retire, and Generation Z talent has joined the workplace. Employee Experience (EX) is critical for organizations to gain a competitive advantage in the labor market by attracting and retaining top talent, which improves business outcomes. The thesis is to study and understand the expectations, Employee Value Propositions (EVPs), and EX of Generation Z employees working in an Austrian electronic company. Design and methods – A quantitative case study was utilized with an anonymous survey conducted on 142 Generation Z employees in the case study company. The survey collected demographic and professional information, and participants were asked their opinions regarding the EVPs and physical, cultural, and technological environment in the EX questionnaire. An EX questionnaire by (Morgan, 2017) evaluated three environmental clutters with 17 questions. Findings – There were 70 responses from 142 participants, with three incomplete attendees. The final sample is 67. The top three EVPs the Gen Zers ranked as most significant to retain them working in the organization are 1) relationships with co-workers, 2) flexibility at work, and 3) job satisfaction. Having competent, innovative, and customer-oriented employees make a company stand out from its rivals in terms of " winning the war for talent”. Success depends on attracting, motivating, and keeping a talented workforce. Regarding the Employee Experience Scores, the statistical results show no differences between males and females of the ExS. Regarding the two age groups, the result shows no differences between age groups in the physical and technical environment dimensions. However, the ExS of Culture is higher in those between 24 and 28 years compared to younger employees of Gen Z. The results also show no difference between the employees in the different positions regarding the ExS in any of these dimensions. Based on the Spearman correlations tests results, it can be concluded that as the education level of employees increases, the perception of the experience with the physical aspects also increases. Besides, there is no relationship between the dimensions of ExS and the age of employees. As the tenure year in the company increases, the perception of experience in physical, cultural, and technical dimensions decreases. The Employee Experience Score of Gen Z employees at the case study company showed positive in the physical environment score and the cultural score, with a negative technology score compared with the average world ExS researched by Morgan. However, lower overall ExS and physical, cultural, and technical scores matched the ExS of Red Bull. And lower physical and technical scores analysis with Intel.Originality/value – Conducted, analyzed, and compared the Employee Experience Index by Morgan to identify the improvement opportunities in the case study company, which provided the statistical data for future practitioners and researchers to design EX strategy in organizations or more profound research.